New Regions and Public Investment in Chile: The Case of Los Rios and Arica y Parinacota Regions (Revista LIDER, 2020)
In recent years, in Chile, there has been a debate on the creation of new administrative regions. This paper analyzes the impact of the creation of Arica and Parinacota and Los Ríos Regions and their residual spaces (Tarapacá and Los Lagos Regions), in regards to its effectiveness in public investment and its relationship with socio-economic indicators. By statistical data processing, we conclude that the creation of these two new regions made possible an increase of the public investment per capita without jeopardizing the residual spaces. In addition, there would not be a consistent relationship between the increase in total public regionalized investment and other indicators. However, we noted a strong relationship between local public investment (regional decision) and wellbeing indicators.